2012
DOI: 10.3109/01677063.2012.700266
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of Heat and Attraction to Optogenetically Induced Sugar Sensation as Operant Behavior in AdultDrosophila

Abstract: Animals have to perform adequate behavioral actions dependent on internal states and environmental situations, and adjust their behavior according to positive or negative consequences. The fruit fly Drosophila melanogaster represents a key model organism for the investigation of neuronal mechanisms underlying adaptive behavior. The authors are using a behavioral paradigm in which fruit flies attached to a manipulator can walk on a Styrofoam ball whose movements are recorded such that intended left or right tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Previous work has demonstrated that the PER can be elicited with ChR2-wt when high light intensities are used (6.5 mW/mm 2 at 480 nm) and flies are starved before the experiment (30). Both ChR2-T159C and ChR2-XXL triggered a PER in satiated flies using considerably lower light intensities (Fig.…”
Section: Significancementioning
confidence: 99%
“…Previous work has demonstrated that the PER can be elicited with ChR2-wt when high light intensities are used (6.5 mW/mm 2 at 480 nm) and flies are starved before the experiment (30). Both ChR2-T159C and ChR2-XXL triggered a PER in satiated flies using considerably lower light intensities (Fig.…”
Section: Significancementioning
confidence: 99%
“…Although visual place learning has been demonstrated in freely walking flies in 2D environments [43], studies of visual conditioning in head-fixed flies have relied on 1D environments in which flies are trained to avoid aversive heat by orienting toward certain visual cues [61]. Our paradigm relied on optogenetically stimulating heat sensing neurons, but the detailed knowledge of —and genetic access to— sensory and reinforcement pathways in Drosophila should permit the generation of other “virtual” sensory stimuli using optogenetics [35, 62, 63]. Using optogenetically-generated virtual stimuli offers significant advantages for experimental design by enabling the creation of sensations in flies that might otherwise affect their state of health (for example, heat, which can physically damage a fly’s body, or sugar, which might satiate it).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, in the fruit fly behavioural field probabilistic reward foraging decision making tasks are missing. Although pavlovian and operant tasks have been extensively used in the fruit fly learning field [48][49][50], these studies do not typically control the value on a continuous scale. Different from learning paradigms, the manipulation of value is necessary to understand what decision variables drive animals' choices on a trial by trial basis.…”
Section: Plos Onementioning
confidence: 99%